Triaxial strength and failure criterion of ultra-high performance concrete. Issue 9 (July 2022) - Wu, Pengtao; Wu, Chengqing; Liu, Zhongxian; Xu, Shenchun; Li, Jun; Li, Jie
Over the past few decades, ultra-high performance concrete (UHPC) has been widely studied and applied because of its outstanding mechanical properties. A large number of studies have been conducted on the uniaxial static and dynamic performance of UHPC materials, however, limited investigations exist on the triaxial compression properties of UHPC. In this study, 98 cylindrical samples of UHPC with different steel fiber volumetric ratios (0.0%–1.5%) were tested to investigate the triaxial behavior of UHPC under different confining pressures (0 MPa–40 MPa). The confining pressure and steel fiber contents have clear impact on the triaxial strength, failure mode, crack width, and the angle between the oblique crack and the axial direction. The triaxial compressive strength and compressive toughness of UHPC subjected to various confining pressures are obtained from the tests and discussed in the study. Based on the testing data, the triaxial compression failure criterion of UHPC is established according to the unified strength theory. Finally, the simplified empirical equations for the full stress-strain curves of UHPC specimens subjected to uniaxial and multiaxial loads are derived, and good agreement with the experimental results is achieved.